PREVENTING VIOLENCE AMONG ADOLESCENTS IN SCHOOL - Gergana Petrova (Peytchinski Publishing, 2020)
Purpose: The present study aims to examine the violence among adolescents at school and outlines opportunities for preventing it. Materials and Methods: The study was conducted at 17 schools on the territory of Plovdiv in two consecutive academic years: 2015/16 and 2016/17. Regular pupils are aged 11-14 years old. For the purpose of the study, have been requested on a regular basis for the number of regular pupils from 5th to 8th grade by grade and sex on the territory of the city of Plovdiv. 302 students were enrolled in the general study. Results: More than half of 153 (55.6%) of respondents said that they had suffered stress during the last year of their life, most often related to divorce of their parents, close-to-birth death, relative` illness, relocation to another town, also moving to another school. These stressful situations in 162 (58.9%) of teenagers are related to the school. There had been more of these situations for girls 83 (63.4%) than for boys 79 (54.9%). More than half of the students 158 (57.5%) had been shown aggression or been witnessed. The results are the same for both sexes. Conclusions: Girls have been objects of aggressionand undergone more stress at school than boys. The main mechanisms for coping with stress and aggression in school are different in boys and girls. The boys said that they do it by themselves and part of the girls through a conversation with the family. A relatively small proportion has indicated the role of the school and school psychologist.